Immunization against αIIbβ3 and αvβ3 in Glanzmann thrombasthenia patients carrying the French Gypsy mutation. (18th November 2020) - Fiore, Mathieu; Bayat, Behnaz; Phuangtham, Roongaroon; Blouin, Laura; Huguenin, Yoann; Bein, Gregor; Santoso, Sentot
Abstract : Essentials The c.1544+1G>A mutation was identified in Gypsy Glanzmann thrombasthenia (GT) patients. Gypsy GT patients express normal αv β3 carrying HPA‐1b epitopes. To demonstrate HPA‐1a alloimmunization by modified antigen capture assays. Gypsy GT patients could develop anti‐HPA‐1a alloantibodies against β3 and αv β3 . Abstract: Background: Glanzmann thrombasthenia (GT) is a rare bleeding disorder caused by the absence or the dysfunction of the platelet αIIb β3 integrin. A founder mutation in the ITGA2B gene was previously identified in French Gypsy patients. Interestingly, this mutation was strongly linked to the human platelet antigen‐1b (HPA‐1b). The HPA‐1bb Gypsy patients are at risk of isoimmunization against αIIb β3, as this complex is not expressed at their platelet surface. Tentatively, they would, however, not have an increased risk of developing anti‐HPA‐1a alloantibodies by exposure of αIIb β3 on platelets from random platelet transfusions. However, the β3 chain can also associate with the αv subunit expressed at the platelet surface. Because Gypsy GT patients express normal αv β3 carrying HPA‐1b epitopes, these patients might develop anti‐HPA‐1a alloantibodies reacting with αv β3 and/or β3 . Objectives/Patients/Methods: To demonstrate this hypothesis, sera from HPA‐1bb (n = 5) and HPA‐1ab (n = 1) Gypsy GT patients were investigated by modified antigen capture assay using platelets or stable transfected cells. Furthermore, stable transfected cells expressing either αIIb β3 or αv β3 together with soluble monomeric chimeric β3 (as absorbent) were used to differentiate anti‐β3 and anti‐αv β3 reactivity. Results: Only HPA‐1bb patients developed alloantibodies reacting with HPA‐1a cells. Further analysis showed that HPA‐1bb patients developed anti‐HPA‐1a alloantibodies reacting with β3 and/or αv β3 . Conclusion: In this study, we found that HPA‐1bb patients who failed to express αIIb β3 on the platelet surface can develop alloantibodies against HPA‐1a reacting with β3 as well as αv β3 . This is of particular importance as anti‐HPA‐1a alloantibodies might cause fetal neonatal alloimmune thrombocytopenia and/or platelet transfusion refractoriness.